The Temple Of The Ruby Of Fire - Geronimo Stilton
It was my most thrilling adventure yet! My old friend Professor von Volt had discovered the location of the famous Ruby of Fire. And before I could let out a squeak of protest, my sister Thea had dragged me into race to be the first to find the legendary gem. The jewel was protected by thousands of ancient booby-traps -- a 'fraidy mouse's worst nightmare? Would I make it through with my fur?